On the design of Remote Health Monitoring System - Mohanad Abdulhamid; Muchisu Albert (Journal of Biomedical Science and Bioengineering, 2021)
With improvement in technology and miniaturization of sensors, there have been attempts to utilize the new technology in various areas to improve the quality of human life. One main area of research that has seen adoption of the technology is the healthcare sector. The people in need of healthcare services find it very expensive, this is particularly true in developing countries. With improvement in technology previously expensive hospital equipment have been redesigned using current technology. The developments have seen a trend known as remote healthcare or previously known as Telemedicine. As a result, this paper is an attempt to solve a healthcare problem facing the society. The main objective of the paper is to design a remote healthcare system. It is comprised of three main parts. The first part being detection of a fall, second being detection of electrocardiogram commonly referred to as ECG or EKG( heartbeat detection) and the last part is providing the detected data for remote viewing. Remote viewing of the data enables a doctor or health specialist to monitor a patient’s health progress away from hospital premises.